28.2k views
1 vote
24 ÷ [ 33- (1+2)^2] = ?

21 + 3 (2-2^2) = ?

[(14+
\sqrt 4)÷2^3] - 14 = ?

20 + [18÷(4+1)] - (3^2 + 2) = ?

please simplify the expressions using the proper order of operations.

User TornadoAli
by
4.9k points

1 Answer

1 vote

Answer:

Below in bold.

Explanation:

24 ÷ [ 33- (1+2)^2]

= 24 / ( 33 - 3^2)

= 24 / 24 = 1.

21 + 3 (2-2^2)

= 21 + 3(2 - 4)

= 21 + 3 * -2

= 21 - 6

= 15.

[(14+√4)÷2^3] - 14

= [ (14 + 2) / 8] - 14

= 16/8 - 14

= 2 - 14

= -12.

20 + [18÷(4+1)] - (3^2 + 2)

= 20 + [18÷ 5] - (9 + 2)

= 20 + 3.6 - 11

= 23.6 - 11

= 12.6.

User John Small
by
4.8k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.